Staff User Attitude towards Overdue Fines in two Nigerian University Libraries - Adeniran, Pauline (MiddleBelt Journal of Library and Information Science, 2013)
This research is conducted to find out the attitudes of staff users towards overdue fines in Nigeria Academic libraries. Redeemer’s University and Ajayi Crowther University both in Nigeria were used as subjects for the study. The instruments used for collecting data for the study were questionnaire, oral interview and observation. The sampled population of the study was teaching and research staff who were available as at the time this research was conducted. A total of 100 questionnaires were administered. Data was analyzed using descriptive statistics. Findings revealed the users’ opinions and feelings about overdue fines. No significant difference was found between either university libraries with respect to their users’ attitude toward overdue fines. This paper makes recommendations that can help libraries boost the collection of overdue fines.